Understanding Value Creation in Digital Companies – A Taxonomy of IoT-enabled Business Models - Woroch, Robert; Strobel, Gero (Proceedings of the 29th European Conference on Information Systems (ECIS 2021), 2021)
The spread of the Internet of Things offers companies the potential to exert a disruptive influence on existing market structures and entire domains. The shift from product to service orientation and the integration of the customer as a value co-creator makes the identification and development of value-adding, IoT-based offerings a central challenge. As a link between strategy and business processes, business models are a suitable tool to meet this challenge. However, present business models lack of consideration of IoT specific characteristics. Against this background we provide a taxonomy for the description of IoT-based business models based on systematic literature research. Furthermore, the taxonomy is applied to 103 business models, demonstrating its usefulness. We also provide insights into the design of business models within two domains. The taxonomy provides a tool for investigating busi-ness models, especially how IoT can be incorporated into them and also a conceptual basis for future research.
Keywords: Digital Value Creation; Internet of Things; Business Model; Taxonomy